A water quality survey of Cameron Highlands watershed. - Suki , A.; M. Jaffar, Maizura
A water quality survey of Cameron Highland's watershed were carried out during a rainy season. Both the rivers and lake in the area were sampled. The highlands's main activities were agriculture and tourism . The water quality parameter investigated includes,BOD,COD,suspended solids,nitrogen compound,phosphorus,pH and dissolved oxygen. The deterioration in water quality were mainly due to suspended solids and nutrient content. This derive mainly from the agriclutural activities. Suspended solids in the rivers ranged mostly between 100 to 300mg/1 but a maximum of 2700mg/1 were detected. The nutrient level were mainly above the criteria recommended for lakes and rivers.